Laying hens prefer softer over harder mineral-based pecking stones and peck them more at the end of the light period - Madeleine McAuley; Linda J. Caston; Tina M. Widowski (Poultry Science)
Mineral-based pecking stones (PS) are edible enrichments for poultry that comprise a high proportion of calcium. We aimed to determine whether laying hens prefer a Soft (easier to ingest) versus a Hard mineral-based PS with the same calcium content, if pecking at PS follows a diurnal pattern similar to calcium appetite, and whether the PS affects eggshell quality. Shaver White laying hens housed in groups of 3 in furnished cages (N = 38) were given either a Hard or Soft PS for 15 days, followed by a 6-day washout period of no PS, and then the opposite PS type for an additional 15 days (Phase 1). After a second 6-day washout period, all cages received both Hard and Soft simultaneously for a 14-day preference test (Phase 2). PS disappearance was quantified by weighing. PS pecking and feeding behaviors were quantified from video recordings of 20 cages scanned at 15 min intervals for 2 days in each treatment period. Egg weights, shell breaking strength and thickness were determined 4 times in Phase 1. In Phase 1, disappearance increased from the first to second period (P = 0.001) and was even greater when the hens had been given Hard then Soft, compared to the opposite sequence (P = 0.0229). PS-pecking was also greater in the second treatment period compared to the first (P = 0.0027). In Phase 2, Soft disappearance was greater than Hard (P < 0.0001), but PS-pecking at the Soft was only greater than that of the Hard when the hens had received the Hard-Soft sequence in Phase 1 (P = 0.0061). The hens showed more PS-pecking behavior towards the end of the light period (∼15:00-18:00) (P < 0.0001). Both eggshell breaking strength (P < 0.0001) and thickness (P = 0.0001) were affected by treatment period suggesting improvement in eggshell quality as ingestion of PS increased. This study shows that hens’ previous experience with PS influenced their use. It provides some evidence that hens’ use of PS is related to their diurnal calcium appetite and affects eggshell quality.